Existence of solutions to discrete and continuous second-order boundary value problems via Lyapunov functions and a priori bounds - Christopher Tisdell; Yongjian Liu; Zhenhai Liu (Electronic Journal of Qualitative Theory of Differential Equations, 2019)
This article analyzes nonlinear, second-order difference equations subject to "left-focal" two-point boundary conditions. Our research questions are: